ANALYZING TRIALS THROUGH ONLINE MEDIA DURING THE COVID-19 PANDEMIC IN INDONESIA - Angga Putra Pratama; Dewa Gede Pradnya Yustiawan (Transpublika Publisher, 2022)
The Corona Virus (Covid-19) pandemic is a challenge for humans to transform life activities, so that people have to adapt to changes in human activities, along with the addition of positive cases of the Covid-19 corona virus, the government enforces the Work from Home (WFH) policy. Likewise, the judicial apparatus must carry out its obligations to carry out trials, with the existence of online court media being an alternative in conducting virtual trials/teleconferences, this is a new breakthrough in conducting trials. So that people get justice and the right to get a legal process Keywords: the judge, online media, Corona Virus (covid-19)